Oxides of nitrogen (nox) abatement using photocatalytic activity of titanium dioxide (Ti02) (Pengurangan Oksida Nitrogen (NOx) Menggunakan Aktivitas Fotokatalitik Titan Dioksida (Ti02) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRAK Oxides of nitrogen such as nitric (NO) and nitrogen dioxide (NO2) are important air pollutants, because they have significant harm to human health and play an important role of being precursor of another dangerous pollutants such as formation of photochemical smog. Anthropogenic activities hold biggest responsibilities for the increasing of NOx concentration in the ambient air. Some stationary sources such as power plant and chemical plant processes emit considerable amounts of NOx to the ambient air. To anticipate the rapid increase of NO, concentration, it is important to develop an alternative technology in NOx abatement until it can be released from the anthropogenic activities within allowable harmless concentration. The catalytic process using uv light and semiconductor particles is a promising alternative of abatement. The semiconductor particles such as titanium dioxide has been widely used as catalyst within various studies of photocatalytic reaction to treat gas pollutants. Photocatalytic activity depends on various characteristic of the materials used as catalyst, since the photocatalytic reaction is a synergy from various.properties contained within the catalyst itself. In fact, treatment of pollutants related to environmental problems through photoassisted catalyst has been a much discussed topic in today's literatures, since efficient utilization of solar light for various emission control processes can save the consumption of fossil fuels. The result of the research showed that the illuminated anatase TiO2 particles with the content of pure TiO2 of 80.42% were able to reduced NOx to the significant value. Only TiO2 particles which absorb photon from uv light are powerful enough to activate the photocatalytic activities. TiO2 powders which was coated on the annular reactor wall showed much better photocatalytic activities compared to the TiO2 granules, because uv light was more uniformly absorbed in TiO2 powders. Actually, TiO2 granules have considerable ability of adsorbing pure NON, but the usage of illuminated TiO2 powders may minimize the quantity of the catalyst in reduction similar NOâ concentration.